2020
DOI: 10.1038/s41598-020-65528-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corrected Inflammation, Oxidative Stress and Endothelial Dysfunction on Fmd Levels in Patients with Selected Chronic Diseases: A Quasi-Experimental Study

Abstract: While the pathophysiology of chronic disorders varies there are three basic mechanisms-inflammation, oxidative stress and endothelial dysfunction-that are common in many chronic diseases. However, the failure of these mechanisms to work synchronously can lead to morbidity complicating the course of many chronic diseases. We analyzed data of 178 patients from cohorts with selected chronic diseases in this quasi-experimental study. Endothelial dysfunction was determined by flow-mediated dilatation (FMD) and asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 46 publications
5
25
0
Order By: Relevance
“…Elevated inflammatory response and increased proteinuria are considered among the important causes of this increased risk 12 . Our previous studies also revealed that vascular inflammation and endothelial dysfunction are the main contributors for CVD events in this patient populations 7 , 13 15 .…”
Section: Introductionsupporting
confidence: 58%
“…Elevated inflammatory response and increased proteinuria are considered among the important causes of this increased risk 12 . Our previous studies also revealed that vascular inflammation and endothelial dysfunction are the main contributors for CVD events in this patient populations 7 , 13 15 .…”
Section: Introductionsupporting
confidence: 58%
“…[14][15][16][17][18][19][20][21][22][23][24][25] Various imaging methods and biochemical biomarkers, including serum endocan, are used to detect endothelial dysfunction. 26 Serum endocan levels have been reported to increase in diseases with endothelial dysfunction. [6][7][8][9] Morbidity and mortality in COVID-19 infection can be explained by the destruction of the endothelial tissue, thromboinflammation, and emboli that develop after thromboinflammation.…”
Section: Discussionmentioning
confidence: 99%
“… 14 - 25 Various imaging methods and biochemical biomarkers, including serum endocan, are used to detect endothelial dysfunction. 26 Serum endocan levels have been reported to increase in diseases with endothelial dysfunction. 6 - 9 …”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of TORC1 , high levels of branched chain amino acids (BCAAs), inflammation, and mitochondrial dysfunction characterize Hp infection [ 47 , 48 , 49 , 50 ]. The same traits also characterize type 2 diabetes (T2D), obesity (OB), Alzheimer’s disease (AD), and cardiometabolic disease (CMD) [ 51 , 52 , 53 ]. These results stimulated further work to determine whether Hp has a role in these diseases [ 14 ].…”
Section: Hp and Metabolic Diseasesmentioning
confidence: 99%